Differentiation of floral color and odor in two fly pollinated species of Metrodorea (Rutaceae) from Brazil - Pombal, Ellen C. P.; Morellato, L. Patrícia C. [UNESP] (Springer Nature, 2000)
We investigated if differences in morphological characters in two species of Metrodorea (Rutaceae) from Brazilian semideciduous forests correspond to some pollination divergence. M. nigra and M. stipularis are sympatric species, display a similar floral morphology, are protandrous, self-incompatible, their flower periods overlap, and both are pollinated by flies. M. nigra main pollinators are Pseudoptiloleps nigripoda (Muscidae) and Fannia sp. (Fanniidae); M. stipularis major pollinators are Phaenicia eximia (Calliphoridae), Palpada sp. and Ornidia obesa (Syrphidae). The distinct floral odor (disagreeable in M. nigra and sweet in M. stipularis) and color (brownish violet vs. pale yellow) determine the differences on type and number of floral visitors observed. Several species from semideciduous forests initially considered to be pollinated by diverse insects, present flies as main pollinators, stressing the importance of fly pollination in such habitats.
Keywords: Brazil; Calliphoridae; Dichogamy; Fanniidae; Floral biology; Metrodorea; Muscidae; Myiophily; Phenology; Pollination; Rutaceae; Semideci duous forest; Syrphidae; Tropical forest; Fannia; Metrodorea nigra; Metrodorea stipularis; Ornidia obesa; Palpada; Phaenicia eximia; Pseudoptiloleps nigripoda